Drivers of deadwood decay of 13 temperate tree species are similar between forest and grassland habitats - Kipping, Lydia; Maurer, Florian; Gossner, Martin M.; Muszynski, Sarah; Kahl, Tiemo; Kellner, Harald; Weiser, Wolfgang W.; Jehmlich, Nico; Noll, Matthias (Frontiers in Forests and Global Change, 2022)
Deadwood provides an important carbon source in forest and wooded ecosystems and, accordingly, forest management strategies discuss the enrichment of deadwood amount and diversity by different tree species. To investigate the decomposition processes of enriched deadwood, we simultaneously placed 3669 size-standardized and gamma sterilized wood specimens of 13 tree species (Populus tremula, Tilia cordata, Prunus avium, Betula pendula, Carpinus betulus, Fraxinus excelsior, Quercus robur, Fagus sylvatica, Acer platanoides, Larix decidua, Pinus sylvestris, Picea abies, and Pseudotsuga menziesii) at a total of 300 forest and grassland plots in three regions of Germany covering large gradients of management intensity and environmental conditions. After one year, mass loss was calculated and its relationship with wood traits and environmental conditions was assessed to determine the most important factors. Mass loss was overall higher in forest compared to grassland habitats, with wood traits as the most important driver, followed by region and environmental factors related to microclimate. However, management intensity was less relevant to explain the mass loss in both habitats. Our results suggest that enriched deadwood, even with removal of endophytes, is subject to the same deadwood degradation drivers as naturally occurring wood. Furthermore, due to the immense and standardized experimental setting, our study contributes to a better understanding of the important drivers of mass loss in different tree species and thus provides the basis for predictions of the carbon cycle in a changing world.